Crosstalk Between Tumor-Associated Microglia/Macrophages and CD8-Positive T Cells Plays a Key Role in Glioblastoma - Tu, Sheng; Lin, Xu; Qiu, Jili; Zhou, Jiaqi; Wang, Hui; Hu, Shiyao; Yao, Yihan; Wang, Yali; Deng, Yongchuan; Zhou, Yunxiang; Shao, Anwen (Frontiers in Immunology, 2021)
Glioblastoma is considered to be the most malignant disease of the central nervous system, and it is often associated with poor survival. The immune microenvironment plays a key role in the development and treatment of glioblastoma. Among the different types of immune cells, tumor-associated microglia/macrophages (TAM/Ms) and CD8-positive (CD8+) T cells are the predominant immune cells, as well as the most active ones. Current studies have suggested that interaction between TAM/Ms and CD8+ T cells have numerous potential targets that will allow them to overcome malignancy in glioblastoma. In this review, we summarize the mechanism and function of TAM/Ms and CD8+ T cells involved in glioblastoma, as well as update on the relationship and crosstalk between these two cell types, to determine whether this association alters the immune status during glioblastoma development and affects optimal treatment. We focus on the molecular factors that are crucial to this interaction, and the role that this crosstalk plays in the biological processes underlying glioblastoma treatment, particularly with regard to immune therapy. We also discuss novel therapeutic targets that can aid in resolving reticular connections between TAM/Ms and CD8+ T cells, including depletion and reprogramming TAM/Ms and novel TAM/Ms-CD8+ T cell cofactors with potential translational usage. In addition, we highlight the challenges and discuss future perspectives of this crosstalk between TAM/Ms and CD8+ T cells.